The association between working posture and work duration with symptoms of Carpal Tunnel Syndrome (CTS) among online motorcycle taxi drivers in Medan City - Latifah, Latifah; Hartono, Hartono; Sinurat, Buenita; Kurniati, Lina; Damanik, Yan Raja David Hamonangan (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Carpal Tunnel Syndrome (CTS) is a neurological disorder caused by compression of the median nerve, commonly observed among workers performing repetitive movements. Online motorcycle taxi drivers represent a high-risk group due to demands for extended working hours and non-ergonomic riding postures. This study aimed to analyse the association between working posture, working duration, and complaints of CTS among online motorcycle taxi drivers. This observational analytical study employed a cross-sectional design and involved 92 online motorcycle taxi drivers in the Universitas Prima Indonesia area, Medan, selected via consecutive sampling. Data were collected using a characteristics questionnaire, the Boston Carpal Tunnel Questionnaire (BCTQ), Phalen's Test, and posture observation using the Rapid Upper Limb Assessment (RULA). Data were analysed using the Chi-Square test. Results indicated that 57.6% of respondents reported CTS complaints. The majority of respondents worked longer than 8 hours per day (66.3%) and had low-risk working postures (48.9%); however, the proportion of CTS was highest among those with high-risk postures (72.4%). Statistical analysis revealed a significant association between working posture and CTS occurrence (p=0.041) and between working duration and CTS occurrence (p=0.009). Working longer than 8 hours per day conferred a 3.2-fold increased risk of developing CTS. It is concluded that poor working posture and prolonged working duration are significantly associated with a higher incidence of CTS among online motorcycle taxi drivers. Ergonomic interventions, regulation of working hours, and occupational health education are recommended for prevention.